Possible Interruption of Measles Virus Transmission, Uganda, 2006–2009 - Baliraine, Frederick N.; Bwogi, Josephine; Bukenya, Henry; Seguya, Ronald; Kabaliisa, Theopista; Kisakye, Annet; Mbabazi, William B.; Sheilagh, B. Smit (Emerging Infectious Diseases, 2011)
To determine what measles virus genotype(s) circulated in Uganda after strategic interventions aimed at controlling/eliminating measles, we examined samples obtained during 2006–2009 and found only genotype B3.1, which had not been previously detected. Kenya was the likely source, but other countries cannot be excluded